Teachers’ Strategies In Increasing Students’ Motivation In On-Line English Learning At UPT SMK Negeri 1 Parepare - Muhammad Ayyub; Nasrullah; Sudarmanto (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
The COVID-19 pandemic situation made the Government announce the learning activities into on-line learning. This research focused on the teachers’ strategies used in increasing students’ motivation in english on-line learning classes. This study aimed at answering the following research questions: (1) what are the teachers’ strategies in increasing students’ motivation in english on-line learning at UPT SMK Negeri 1 Parepare? (2) To what extent do the strategies help the teachers in English on-line classes? This type of research was field research with qualitative approach. The results showed that (1) There were several strategies used by English teachers in increasing student motivation in learning English online. The strategies include: using news text, using dialogue text, doing personal approach, giving students the praise/reward, and make a video. (2) Strategies in teaching through on-line learning classes during the COVID-19 pandemic greatly assisted teachers in the increasing motivation students in teaching and learning process to achieve learning goals.